PENGARUH KUALITAS PRODUK DAN CITRA MEREK KOSMETIK SOMETHINC TERHADAP MINAT BELI GENERASI Z MELALUI TIKTOK SHOP DI KOTA BANDUNG - Wa Ode Agla Roza; Bangkit Nuratri (CV. Denasya Smart Publisher, 2025)
The development of the beauty industry is currently experiencing a rapid rise. This results from numerous elements, among them being the awareness to look attractive. Various cosmetic brands create products by following the development of existing beauty trends in order to attract consumer attention. In attracting consumer buying interest, business actors must pay attention to several factors, including product quality and brand image. The objective of this investigation was to pinpoint and scrutinize the influence of item excellence and brand image of Somethinc cosmetics on Generation Z's buying interest through Tiktok Shop in Bandung City. The method used employs a numerical technique with an explanatory and validation strategy. This research utilizes original and secondary data gathered through surveys given to from participant who meet predetermined criteria. The group targeted in this research consists of Gen Z residing within Bandung City and have the desire to buy Somethinc cosmetic products through Tiktok Shop, the number of which cannot be known with certainty. Determination of the specimen for this research applying the Cochrane equation therefore 96 respondents were obtained as the research sample. Within this research, information handling and examination were performed via authenticity assessments, dependability checks, traditional premise evaluations, plural linear regression scrutiny, determination coefficient evaluations, and supposition appraisal employing support of SPSS software version 25. The outcomes of this research reveal that merchandise excellence separately bears no impact and is trivial toward buying interest, brand image separately exerts a meaningful influence upon buying interest, and merchandise excellence along with brand image collectively exert a meaningful influence upon buying interest. This research discovered that the impact products quality and brand image of Somethinc cosmeticson generation z’s purchasing interest through tiktok shop in Banding city, amounting to 42,6%.